Using 3D printing to implement a hyperthermia insert for a preclinical MPI scanner (Transactions on Additive Manufacturing Meets Medicine, 2020)
Magnetic particle imaging (MPI) is a rapidly developing imaging modality, which determines the spatial distribution of magnetic nanoparticles. Magnetic fluid hyperthermia (MFH) is a promising therapeutic approach where magnetic nanoparticles are used to transform electromagnetic energy into heat. The similarities of MPI and MFH give rise to the potential of integration of MFH and MPI. 3D printing is used for the manufacture of an oil-cooled MFH insert. The design and the implementation of a MFH insert for a preclinical MPI scanner is presented in this paper.
Keywords: magnetic particle imaging; hyperthermia